Composite indicator for green city development in Singapore - Ling, Xue Mian (Nanyang Technological University, 2024)
Amid the global challenges of climate change and warming, governments worldwide have increasingly prioritised green growth strategies, with Singapore being no exception. However, Singapore's rapid urbanisation and limited land resources present unique obstacles to environmental conservation. This research aims to evaluate Singapore's advancements in becoming a green city by building upon the methodologies outlined in Lee and Chou (2018) and developing a set of tailored green city indicators aligned with the Driving Force, Pressure, State, Exposure, Effects, and Action (DPSEEA) model. Through the application of principal component analysis (PCA) and common factor analysis (CFA), the study will assess Singapore's journey towards achieving a green and sustainable future, culminating in the creation of an aggregated composite index. Following this, sensitivity analysis was conducted to offer further insights into the robustness of the findings. Lastly, this research identifies key areas for policy intervention, which hopefully help Singapore to accelerate its progress towards becoming a fully-fledged "green city".